THE CONCEPT OF UNEXPECTED TIME AND SPACE IN THE NOVEL "MING BIR QIYOFA" (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article investigates the problem of artistic chronotope in the novel "Ming bir qiyofa" by the author Omon Mukhtor. The artistic and aesthetic function of clarifying the real chronotope features of unexpected time and space are specifically stressed It comparatively studies the commonalities between realistic and nonrealistic realities of space discussing the author's ideological and artistic intentions, poetic skills and gives concluding remarks.